The Influence of Limited Facilities and Utilization of Digital Technology on the Effectiveness of Geography Learning at SMA Negeri 1 Stabat - Claudia Grace Natasya Simarmata; Mutiara Cristeofani Hutauruk; Riski Fanni Lumban Gaol; Syarifah Andini (Sean Institute, 2024)
This study aims to explore the influence of limited facilities and digital technology utilization on the effectiveness of geography learning at SMA Negeri 1 Stabat. The method used was qualitative, with data collection through interviews and observation. The results show that limited facilities, such as practical tools and books, have a negative impact on the achievement of learning objectives. However, the utilization of digital technology has helped improve the learning process, although there is still a mismatch between learning needs and facility availability. The findings emphasize the importance of optimizing existing facilities and integrating technology to improve geography learning effectiveness .